Dyslipidemia in hypothyroid patients of Rajshahi Medical College Hospital - Basak, PM; MMR, Khan; Rahman, MK; Islam, MN; Afzal, SM; Huda, MN; Das, HS; Sarker, BC; Islam, M Akhtarul; Islam, MT (TAJ: Journal of Teachers Association, 2018)
Hypothyroidism accounts for about 2% all cases of hyperlipidemia. The present study was planned to determine the level of lipid profile in patients diagnosed with hypothyroidism. Patients were screened for T3, T4 and TSH. Based on these values those who were having hypothyroidism were selected. Total 60 cases were selected. Mean ± SD values of total cholesterol was 210.37 ± 23.85, Triglycerides was 199.40 ± 21. 38 and LDL-C was 140.20 ± 26.81. Our study is suggested that dyslipidemia is associated with hypothyroidism. TAJ 2016; 29(1): 49-51